Lower Order and Higher Order Entanglement in Four‐Wave Mixing Process. Issue 1 (27th September 2017) - Das, Moumita; Sen, Biswajit; Ray, Ayan; Pathak, Anirban
Abstract: Possibilities of generation of lower order and higher order intermodal entanglement in four‐wave mixing (FWM) process are rigorously investigated using Sen‐Mandal perturbative technique. The investigation has revealed that for a set of experimentally realizable parameters, one can observe lower order and higher order intermodal entanglement between pump and signal modes and signal and idler modes in a FWM process. In addition, trimodal entanglement involving pump, signal and idler modes is also reported. Abstract : Possibilities of generation of lower order and higher order intermodal entanglement in four‐wave mixing (FWM) process are rigorously investigated using Sen‐Mandal perturbative technique. The investigation has revealed that for a set of experimentally realizable parameters, one can observe lower order and higher order intermodal entanglement between pump and signal modes and signal and idler modes in a FWM process. In addition, trimodal entanglement involving pump, signal and idler modes is also reported.